2017
DOI: 10.1016/j.cellsig.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide and heat stress impair the estradiol biosynthesis in granulosa cells via increase of HSP70 and inhibition of smad3 phosphorylation and nuclear translocation

Abstract: LPS and heat stress have been shown to exert various toxic effects in animals, as they induce estradiol biosynthesis dysfunction in granulosa cells (GCs) and result in low reproductive performance. However, there is limited information regarding their detailed mechanisms. In the present study, primary cultured porcine GCs were treated with LPS (1000ng/mL for 48h), or heat stress (41°C for 3h), in vitro, with or without the HSP70 inhibitor VER155008 (10μM), to investigate their potential mechanisms. To mimic th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 86 publications
0
17
0
Order By: Relevance
“…As reported by previous studies, elevated serum HSP70 is not only involved in the pathogenesis of insulin-resistant disorders, but also in ovarian stress response such as heat shock and malnutrition/serum deprivation in porcine ovarian cells culture [18]. As well as the denote ovarian damage [19], these heat stress could impair estradiol biosynthesis in granulosa cells via increased HSP70 [20], and HSP70 induction in the ovary increases susceptibility to premature ovarian failure due to downregulation of autophagy [7]. In the present study, the serum estradiol levels showed no significant difference between PCOS and control groups, this may due to the high level of testosterone, the precursors of estradiol, can compensate the impaired estradiol biosynthesis by the higher expression of HSP70 in PCOS ovaries.…”
Section: Discussionmentioning
confidence: 89%
“…As reported by previous studies, elevated serum HSP70 is not only involved in the pathogenesis of insulin-resistant disorders, but also in ovarian stress response such as heat shock and malnutrition/serum deprivation in porcine ovarian cells culture [18]. As well as the denote ovarian damage [19], these heat stress could impair estradiol biosynthesis in granulosa cells via increased HSP70 [20], and HSP70 induction in the ovary increases susceptibility to premature ovarian failure due to downregulation of autophagy [7]. In the present study, the serum estradiol levels showed no significant difference between PCOS and control groups, this may due to the high level of testosterone, the precursors of estradiol, can compensate the impaired estradiol biosynthesis by the higher expression of HSP70 in PCOS ovaries.…”
Section: Discussionmentioning
confidence: 89%
“…Long-term heat exposure (HE) has noticeable adverse effects on female mammals. Emerging evidence has confirmed that HE can lead to female endocrine disorders and ovarian dysfunction ( Dickson et al, 2018 ), affect rat ovarian cell proliferation and apoptosis, induce ovarian hormone over secretion ( Sirotkin, 2010 ), destroy hormone balance ( Li et al, 2017 ), increase sensitivity of granulosa cells to apoptosis ( Luo et al, 2016 ), and so on. Many studies reported the damage of HE-induced female reproductive function, yet its mechanism has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In the bovine granulosa cells, LPS binds to toll-like receptor 4 (TLR4) promotes nuclear factor-kB (NF-κB) translocation from the cytoplasm to the nucleus, and increases the levels of pro-inflammatory cytokines such as interleukin-1β (IL-1β), IL-6, IL-8, and tumor necrosis factor (TNF)-α [7,8,9,10]. LPS also inhibits steroid production of bovine or porcine granulosa and theca cells [5, 11,12,13], decreases the expression of gonadotropin receptors and cytochrome P450 family 19 subfamily A member 1 (Cyp19a1) in bovine granulosa and theca cells [11, 14, 15] and perturbs bovine oocyte meiotic progression in vitro [8]. In the mouse liver, pro-inflammatory cytokines, such as TNF-α, IL-1β, and IL-6, and LPS can induce endoplasmic reticulum (ER) stress and causes an acute phase response [16].…”
mentioning
confidence: 99%